2020
DOI: 10.1002/jts.22569
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Trauma Exposure and Chronic Homelessness Among Veterans: The Roles of Responses to Intrusions and Emotion Regulation

Abstract: Veterans with mental health problems and a history of interpersonal and military trauma exposure are at increased risk for chronic homelessness. Although studies have examined posttraumatic stress disorder (PTSD) as a predictor of homelessness, there is limited understanding of specific mechanisms related to cumulative trauma exposure. We sought to elucidate how cumulative interpersonal and military trauma exposure may be linked to homelessness chronicity by examining the role of factors that influence trauma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 68 publications
(82 reference statements)
1
9
0
Order By: Relevance
“…For instance, perhaps there are external explanatory factors about the overall homeless population that contribute to higher incidence of cardiopulmonary ill health, making differences in individuals’ duration of homelessness less than a causal factor. Statistically, there are no reported health differences associated with duration of homelessness, either sheltered or unsheltered individuals, which adds to the literature on this topic [ 19 , 52 , 53 , 54 , 55 , 56 , 57 ]. It also may be the case that even short-term experiences of homelessness contribute substantially to cardiopulmonary concerns, again negating duration as a causal, explanatory factor of differences in reported negative health outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, perhaps there are external explanatory factors about the overall homeless population that contribute to higher incidence of cardiopulmonary ill health, making differences in individuals’ duration of homelessness less than a causal factor. Statistically, there are no reported health differences associated with duration of homelessness, either sheltered or unsheltered individuals, which adds to the literature on this topic [ 19 , 52 , 53 , 54 , 55 , 56 , 57 ]. It also may be the case that even short-term experiences of homelessness contribute substantially to cardiopulmonary concerns, again negating duration as a causal, explanatory factor of differences in reported negative health outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, perhaps there are external explanatory factors about the overall homeless population that contribute to higher incidence of cardiopulmonary ill health, making differences in individuals' duration of homelessness less than a causal factor. Statistically, there are no reported health differences associated with duration of homelessness, either sheltered or unsheltered individuals, which adds to the literature on this topic [19,[51][52][53][54][55][56]. It also may be the case that even short-term experiences of homelessness contribute substantially to cardiopulmonary concerns, again negating duration as a causal, explanatory factor of differences in reported negative health outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have also concluded that ACEs are powerful risk factors and can predict or shed light on pathways into adult homelessness (Caton et al, 2005;Goodman et al, 1991;Hamilton et al, 2011;Hayes et al, 2013;Herman et al, 1997;Roos et al, 2013). Recent research with veterans indicated that cumulative trauma exposure plays a role in future homelessness and that vulnerabilities for homelessness in female veterans were histories of isolation and lack of social support (Hamilton et al, 2011;Macia et al, 2020). Thus, early childhood trauma has an important association with both the incidence and severity of homelessness.…”
Section: Prior History Of Traumatic Eventsmentioning
confidence: 99%
“…Persons experiencing homelessness (PEH) may experience traumatic stress from multiple sources, including structural violence throughout the life course, adverse childhood experiences (ACEs), events leading up to an episode of homelessness, and/or experiences that occur while a person remains unsheltered (Bassuk et al, 2001;Goodman et al, 1991;Los Angeles Homeless Services Authority, 2019;Roos et al, 2013;Young et al, 2017). Repeated or multiple traumatic experiences can overwhelm a person's available internal and/or external resources to such a degree that their physiological reactions interfere with effective coping and they have reduced capacity for emotional regulation (Macia et al, 2020;McVicar, 2003). Additionally, there is evidence to show a correlation between racism, oppression, marginalization, and a history of trauma with lifetime homelessness (Fusaro et al, 2018;Galtung & Fischer, 2013;Jones, 2016;Los Angeles Homeless Services Authority, 2019;Olivet et al, 2019;Roth & Bean, 1986).…”
Section: Introductionmentioning
confidence: 99%